Dampak Erupsi Gunung Merapi Terhadap Nilai Lahan dan Bangunan: Pendekatan Hedonic Price - Endah Saptutyningsih (Teknik Lingkungan Universitas Islam Indonesia, 2011)
This study aims to conduct economic valuation of volcanic eruption impacts in disaster prone areas of Merapi eruption. Economic valuation of flood disaster impacts were calculated using the hedonic price method. The disaster prone areas of Merapi eruption are the area especially located in Sleman Regency, they are Turi, Pakem, Cangkringan, and Ngemplak Districts.The results of this study indicate that the hedonic price method can be applied in Sleman Regency to obtain estimates marginal damage to property value caused by flooding. The significance of height level of deposits of volcanic material coefficient shows that flood is indeed depressing the agricultural land value. The sample household’s average marginal willingness to pay (MWTP) for a unit decrease in height level of deposits of volcanic material in their agricultural land is estimated at a reasonable amount of Rp 653,800.00. By conducting economic valuation in the Sleman Regency, is expected to be also done in other areas vulnerable to volcanic eruption disasters.